Investment Project Analysis For Offshore Complex Hydrocarbon Field Using - Winiarti; Taufik Faturohman (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research is conducted with the following objectives evaluate the feasibility of developing oil and gas fields based on the application of new production techniques in multi-phase fluid reservoirs, to enalyze the primary parameters that distinctly impact the project’s NPV and IRR through sensitivity analysis, to estimate the probability of deficient NPV outcomes through Monte Carlo simulation which applies uncertainty in prices, production, and costs against a scenario of negative NPV, and to evaluate the value of advanced contractor pays as a result of the modified gross split contract in improving the overall project NPV. A quantitative research design is the type of research used in this study. The study finds that the feasibility of developing the GLB Field using advanced production techniques in multi-phase fluid reservoirs is limited under current conditions due to high financial uncertainty. Sensitivity analysis reveals that oil prices, production volumes, and capital expenditures are the primary drivers of NPV and IRR fluctuations. Monte Carlo simulation further confirms a significant probability of negative NPV outcomes, highlighting the project's vulnerability to market volatility. However, modifying the Gross Split PSC to include an additional contractor split substantially improves NPV expectations, indicating that a more flexible fiscal framework can enhance the project's commercial viability.